Autophagy: A Novel Pharmacological Target in Diabetic Retinopathy - Adornetto, Annagrazia; Gesualdo, Carlo; Laganà, Maria Luisa; Trotta, Maria Consiglia; Rossi, Settimio; Russo, Rossella (Frontiers in Pharmacology, 2021)
Autophagy is the major catabolic pathway involved in removing and recycling damaged macromolecules and organelles and several evidences suggest that dysfunctions of this pathway contribute to the onset and progression of central and peripheral neurodegenerative diseases. Diabetic retinopathy (DR) is a serious complication of diabetes mellitus representing the main preventable cause of acquired blindness worldwide. DR has traditionally been considered as a microvascular disease, however this concept has evolved and neurodegeneration and neuroinflammation have emerged as important determinants in the pathogenesis and evolution of the retinal pathology. Here we review the role of autophagy in experimental models of DR and explore the potential of this pathway as a target for alternative therapeutic approaches.